MicroRNA-21 is Associated with the Severity of Right Ventricular Dysfunction in Patients with Hypoxia-Induced Pulmonary Hypertension - Chang, Wei-Ting (Acta Cardiol Sin, 2018)
BACKGROUND: The outcome of pulmonary hypertension (PH) mainly depends on the development of right ventricular (RV) dysfunction, and survival among patients with different etiologies of PH varies. Chronic hypoxia is a major cause of secondary PH, however the mechanisms of its associated RV dysfunction are largely unknown. Herein, we studied the role of microRNA-21 (miR-21) in hypoxia-induced RV dysfunction. METHODS: In this longitudinal, prospective study, we enrolled 41 patients with hypoxia-induced PH. Echocardiography was conducted and circulating miR-21 was measured. The expression of miR-21 was also evaluated in hypoxia-treated human pulmonary microvascular endothelial cells (HPECs) and conditioned media. Through the over-expression of miR-21 in H9C2 cells, we further identified crosstalk between the pulmonary circulation and RV. RESULTS: Among the studied patients, 10 developed RV dysfunction. Notably, the expression of circulating miR-21 was correlated with the severity of RV dysfunction. Likewise, miR-21 was up-regulated in the hypoxia-treated HPECs and its conditioned media in a time-dependent manner. I addition, hypertrophic changes were observed in the hypoxia-treated HPECs. The up-regulation of heart failure-associated markers in H9C2 cells over-expressing miR-21 implied the influence of pulmonary circulatory miR-21 on RV function. CONCLUSIONS: The expression of systemic and pulmonary miR-21 is associated with the severity of RV dysfunction in patients with hypoxia-induced PH.